BANKRUPTCY MODEL EXAMINATION OF HEALTH CARE PROVIDERS - Hegedűs, Mihály (Acta Carolus Robertus, 2021)
The institution that is the subject of the analysis is the Péterfy Hospital-Clinic and Jenő Manninger National Institute of Traumatology. This hospital was chosen to have its situation ana-lyzed, because I had previously done a study on it in conjunction with a bankruptcy model study. I can also examine the occurrence of forecasts and conclusions from previous data by continuing the previous research, and thus the current analysis can cover a longer period, so an even more accurate picture can be obtained for the future of the institution. The examination of the balance sheet data is carried out with the data of the years 2014-2019, the reason for this is that the format and lines of the annual report has changed in 2014, so the comparison of the reports with previous years could be possible by transformation, however, due to size limitations in the present study I do not implement this. The bankruptcy model study has been examining the institution since 2006, as the indicators can also be calculated according to the previous reporting scheme with the appropriate stipulations. In the analysis of assets and liabilities, only those balance sheet lines are presented that have value for the period under review.